KONTRIBUSI DANA PERIMBANGAN APBN DAN PAJAK NBUMI BANGUNAN (PBB) TERHADAP PEMBANGUNAN INFRASTRUKTUR DAERAH DI KABUPATEN JOMBANG (Studi Deskriptif Terhadap Pembangnan Infrastruktur di Kabupaten Jombang Tahun 2015-2017) - Rico Adi Suwardianto; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT               The objectives of this study are: 1) To determine the contribution of the effect of the APBN Balance Fund on infrastructure development in Jombang Regency. 2) To find out the contribution of the Bumi Bangunan (PBB) tax compared to other regional revenues on infrastructure development in Jombang Regency. This research uses descriptive research. Descriptiv0 research is research conducted to determine the value of an independent0variable, either one variable or more without0making comparisons or connecting with other variables.               The results of this study indicate that: 1) Contribution of the State Budget Balancing Fund to Infrastructure development in Jombang Regency. 2) Contribution of Land and Building Tax (PBB) compared to other regional income towards infrastructure development in Jombang Regency. This shows that the contribution of the APBN balance fund and the land and earth building tax (PBB) is very effective.Keywords: APBN Balancing Fund and Land and Building Tax (PBB)